THERAPLAY UNTUK MENINGKATKAN KONSEP DIRI, KEBAHAGIAAN DAN PENGELOLAAN STRESS PADA CALON PEKERJA MIGRAN - Astuti, Sri Wahyuning; Yenny, Yenny; Wardani, Laila Meiliyandrie Indah; Dearly, Dearly; Bustami, Mohammad Reevany (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
To be able to become a worker in a foreign country, of course, one must have sufficient provisions, both skills and the mental condition of the prospective worker. Workers who will be sent abroad must have the skills needed by the intended company. Preparation and improvement of workers' skills, among others, is carried out at the Job Training Institute. Mainstay Job Training Institute, is one of the LPK that prepares workers to be sent, among others, to Japan.This Community Service activity aims to manage the emotions of prospective migrant workers. Efforts to process emotions into positive ones are carried out by Therplay, namely playing as an effort to drive away boredom and increase self-confidence. Some of the game patterns that are carried out are making palm prints using either flour or watercolour.The provision of materials to 100 prospective migrant workers succeeded in increasing self-confidence, creating joy and a comprehensive understanding of the self-concept of each prospective migrant worker.